Research of the present situation and development trend of intelligent coal mine construction market - Lin ZHANG; Guofa WANG; Zhiguo LIU; Jiaxing FU; Dandan WANG; Yaqi HAO; Lingyu MENG; Jianzhong ZHANG; Zhaoyu ZHOU; Liang ZHANG; Jie QIN (Meitan kexue jishu)
The current situation and future development trend of the intelligent construction market in coal mines are the focus of attention for industry management departments, coal production enterprises, technology support enterprises, and other potential enterprises. It is also an important guiding direction for capital investment, technology research and development, and talent cultivation in the industry. Construct a six dimensional Porter diamond model based on production factors, demand conditions, supporting industries, enterprise strategies, industry opportunities, and government support policies to macroscopically analyze the competitive advantages of the coal mine intelligent construction market; Based on historical data such as the number of coal mines, production capacity, fixed assets investment in mining and dressing industry, total investment in intelligent construction, and construction results from 2013 to 2023, select data in different dimensions such as quantity indicators, production capacity indicators, and investment indicators, calculate the market penetration rate of intelligent construction of coal mines and perform curve fitting, and further modify the fitted curve according to the concentration of coal enterprise scale, concentration of coal production capacity distribution, and concentration of coal enterprise attributes; To further measure the market vitality of coal mine intelligent construction, taking the first batch of 71 intelligent demonstration coal mines in China as samples, the market capacity of coal mine intelligent construction from 2025 to 2035 is predicted. In the case where it is difficult to obtain comprehensive and accurate market data of all subsystems of coal mine intelligent construction over the years, SAC, SAM, and SAP product market statistical data are used to verify the reliability of coal mine intelligent market analysis and prediction results; Based on policy guidance, technological status, and actual construction, five stages of the development of the coal mine intelligent construction market have been proposed: budding, cultivating pilot projects, demonstration construction, comprehensive construction, and advanced intelligence. Based on the Jeffrey Moore divide theory, the characteristics of each stage of intelligent construction and the characteristics of early and mainstream markets have been analyzed, and the market gap and its factors in coal mine intelligent construction have been explored. Specific measures to bridge the gap have been proposed. China’s coal mine intelligent construction market has strong and sustained competitiveness; The market penetration rate is expected to reach 10% by 2026, with a market penetration rate of approximately 4.74% in 2023. This is a golden period for social capital investment, and lower investment can be used to leverage higher market share in the future; The market capacity for intelligent construction of coal mines is expected to exceed 320 billion yuan by 2025 and reach trillions of yuan by 2035; The current intelligent construction of coal mines is in a gap area between the early market and the mainstream market, and it is expected to cross the gap in 2−3 years.